2019
DOI: 10.1109/access.2019.2918714
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Visualization of Deep Neural Networks in Device-Free Wi-Fi Indoor Localization

Abstract: Device-free Wi-Fi indoor localization has received significant attention as a key enabling technology for many Internet of Things (IoT) applications. Machine learning-based location estimators, such as the deep neural network (DNN), carry proven potential in achieving high-precision localization performance by automatically learning discriminative features from the noisy wireless signal measurements. However, the inner workings of DNNs are not transparent and not adequately understood especially in the indoor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Nowadays there are many proposals that consider mobility models that predict the motion of a sensor node [3]. In MWSNs, mobility models predict the trajectory of a moving sensor node [1,28]. Mobility models describe the speed changes, acceleration and position of a sensor node with respect to time; and they are often used to investigate new proposals of communication and navigation techniques.…”
Section: Related Workmentioning
confidence: 99%
“…Nowadays there are many proposals that consider mobility models that predict the motion of a sensor node [3]. In MWSNs, mobility models predict the trajectory of a moving sensor node [1,28]. Mobility models describe the speed changes, acceleration and position of a sensor node with respect to time; and they are often used to investigate new proposals of communication and navigation techniques.…”
Section: Related Workmentioning
confidence: 99%
“…In 2019, Liu et al [38] pointed out that deep neural networks have shown great potential in indoor high-precision localization, but the inner principles are not adequately understood. So, they provide quantitative and visual explanations for the deep learning process and the important features learnt by deep neural network during the learning process.…”
Section: Device-free Indoor Localizationmentioning
confidence: 99%
“…Nowadays there are many proposals in regards to mobility models that predict the motion of a sensor node [3]. In MWSNs, mobility models predict the trajectory of a moving sensor node [1], [26]. Mobility models describe the speed changes, acceleration and position of a sensor node with respect to time; and they are often used to investigate new propositions on communication and navigation techniques.…”
Section: Related Workmentioning
confidence: 99%